Effect of Motivation, Work Environment and Leadership on Employee Performance with Work Spirit as Intervening Variable (Economic Education Analysis Journal, 2022)
This study aimed to determine how much the effect of motivation, work environment and leadership on employee performance with work spirit as an intervening variable at Wali Nagari Setara Nanggalo. The method of data collection was by distributing questionnaires to 30 respondents which were distributed to employees at the office of Wali Nagari Setara Nanggalo, Koto XI Tarusan District, Pesisir Selatan Regency. The analytical method used Structural Equation Modeling (SEM) Analysis with Partial Leats Square (PLS) 3. The results showed that motivation had a positive and significant effect on employee performance, work environment had a positive and significant effect on employee performance. Leadership had a positive and significant effect on employee performance, Motivation had a positive and significant effect on work spirit. The work environment had a positive and significant effect on work spirit, leadership had a positive and significant effect on work spirit. Based on the results of this study, it is expected that the employees of the office of Wali Nagari Setara Nanggalo, Koto XI Tarusan District, Pesisir Selatan Regency can improve their performance by improving motivation, work environment and leadership by increasing work spirit.